2019
DOI: 10.1093/treephys/tpz129
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide investigation of WRKY transcription factors in sweet osmanthus and their potential regulation of aroma synthesis

Abstract: WRKY transcription factors, one of the largest transcription factor families, play important roles in regulating the synthesis of secondary metabolites. In sweet osmanthus (Osmanthus fragrans), the monoterpenes have been demonstrated as the most important volatile compounds, and the W-box, which is the cognate binding site of WRKY transcription factors, could be identified in most of the terpene-synthesis-related genes’ promoters. However, the role of the WRKY family in terpene synthesis in sweet osmanthus has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 53 publications
2
22
1
Order By: Relevance
“…Transcription factor CitERF71 activates the terpene synthase encoding gene CitTPS16 involved in the biosynthesis of E-geraniol in Citrus sinensis Osbeck (Li et al 2017). Recently, a genome-wide investigation of WRKY transcription factors in Osmanthus Fragrans indicated potential roles for OfWRKY139 and OfWRKYs with plant zinc cluster domains in regulating biosynthesis of aromatic compounds in sweet osmanthus (Ding et al 2019); A study on monoterpene synthase promoter related transcription factors in Lavandula × Intermedia by yeast one-hybrid assay indicated that multiple transcription factors control monoterpene synthase expression in lavender, including MYB, bZIP, NAC, GeBP and SBPrelated proteins (Sarker et al 2019). In the present work, we identified one WRKY, two BHLH, one AP2/ERF and three MYB candidate genes, which exhibited the same expression pattern as CcTPS5 and CcTPS7.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factor CitERF71 activates the terpene synthase encoding gene CitTPS16 involved in the biosynthesis of E-geraniol in Citrus sinensis Osbeck (Li et al 2017). Recently, a genome-wide investigation of WRKY transcription factors in Osmanthus Fragrans indicated potential roles for OfWRKY139 and OfWRKYs with plant zinc cluster domains in regulating biosynthesis of aromatic compounds in sweet osmanthus (Ding et al 2019); A study on monoterpene synthase promoter related transcription factors in Lavandula × Intermedia by yeast one-hybrid assay indicated that multiple transcription factors control monoterpene synthase expression in lavender, including MYB, bZIP, NAC, GeBP and SBPrelated proteins (Sarker et al 2019). In the present work, we identified one WRKY, two BHLH, one AP2/ERF and three MYB candidate genes, which exhibited the same expression pattern as CcTPS5 and CcTPS7.…”
Section: Discussionmentioning
confidence: 99%
“…WRKY protein sequences in Arabidopsis thaliana were downloaded from UniProt protein database, 6 named as AtWRKY1-AtWRKY 70 (Ding et al, 2020). Subsequently, the Clustal W multiple sequences alignment of CpWRKY ( 19) and AtWRKY (70) proteins was performed using MEGA6 software.…”
Section: Multiple Sequence Alignment and Phylogenetic Analysesmentioning
confidence: 99%
“…Gelsemiaceae (Z)-α-ocimene, α-farnesene [29] Gossypium hirsutum Malvaceae (3S)-linalool GhTPS12 [30,31] Jasminum spp. Oleaceae α-farnesene, linalool, β-ocimene, germacrene-D [32][33][34][35][36] Laurus nobilis Lauraceae sesquiterpenes, γ-cadinene, δ-cadinene [37] Lonicera japonica Caprifoliaceae linalool [38] Magnolia champaca Magnoliaceae (R)-linalool, linalool and its oxides [39] Malus domestica Rosaceae (E)-linalool oxide [40] Murraya paniculata Rutaceae E-β-ocimene, linalool, α-cubebene [41,42] Myrtus communis L. Myrtaceae α-pinene, linalool, 1,8-cineole [43] Osmanthus fragrans Oleaceae linalool and its derivatives, α-ionone, β-ionone OfTPS1, OfTPS2, OfTPS3 [44][45][46][47] Paeonia spp. Paeoniaceae β-caryophyllene, linalool [48,49] Psidium guajava Myrtaceae α-cadinol, β-caryophyllene, nerolidol [50] Rosa spp.…”
Section: Datura Wrightiimentioning
confidence: 99%
“…In O. fragrans flowers, WRKY transcription factors play important roles in regulating the biosynthesis of secondary metabolites. The expression of OfWRKY19/36/84/139 positively correlates with the biosynthesis of volatile monoterpenes; in contrast, the expression of OfWRKY7 negatively correlates with the biosynthesis of volatile monoterpenes [46]. In addition, the OfWRKYs regulate volatile monoterpene biosynthesis in O. fragrans by binding plant zinc cluster domains [45].…”
Section: Wrkymentioning
confidence: 99%